Œuvres poétiques de Marie de Romieu / publiées avec une préface et des notes par Prosper Blanchemain - Romieu, Marie de (1878)
Œuvres poétiques de Marie de Romieu / publiées avec une préface et des notes par Prosper Blanchemain -- 1878 -- livre
Keywords: conditions des femmes*; cours; europe; fem1000; france; histoire des femmes*; histoire et politique; littérature; moyen-âge; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*

Social purity - Anthony, Susan B. (Not For Ourselves Alone | Ken Burns | PBS, 1875)
In the winter of 1875 Miss Anthony prepared her speech on “Social Purity” and gave it first at the Grand Opera House, Chicago, March 14, in the Sunday afternoon Dime lecture course. When she reached the opera house the crowd was so dense she could not get inside and was obliged to go through the engine room and up the back way to the stage. The gentleman who was to introduce her could not make his way through the throng and so this service was gracefully performed by “Long John” Wentworth, who was seated on the stage. At the close of the address, to her surprise, A. Bronson Alcott, Parker Pillsbury and A.J. Grover came up to congratulate her. She had not known they were in the city. Mr.Alcott said: “You have stated here this afternoon, in a fearless manner, truths that I have hardly dare to think, much less to utter.” No other speaker, man or woman, ever had handled this question with such boldness and severity and the lecture produced a great sensation. Even the radical Mrs. Stanton wrote her she would again be asked to speak in Chicago, and Mr. Slayton said that she had ruined her future chances there; nevertheless she was invited by the same committee the following winter.
Keywords: 1800-1899; amériques; approches et analyses; cours; discipline; discours; discours dominant; droits des femmes*; fem1000; histoire; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis